2014
DOI: 10.1073/pnas.1407147112
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome controls alternative splicing to mediate light responses in Arabidopsis

Abstract: Plants monitor the ambient light conditions using several informational photoreceptors, including red/far-red light absorbing phytochrome. Phytochrome is widely believed to regulate the transcription of light-responsive genes by modulating the activity of several transcription factors. Here we provide evidence that phytochrome significantly changes alternative splicing (AS) profiles at the genomic level in Arabidopsis, to approximately the same degree as it affects steady-state transcript levels. mRNA sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
198
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(215 citation statements)
references
References 37 publications
16
198
0
1
Order By: Relevance
“…Both splice isoforms harbor premature termination codons resulting in truncated proteins that retain interaction with CONSTITUTIVE PHOTOMORPHOGENIC 1 (COPI) but lose the ability to bind to DAMAGED DNA-BINDING PROTEIN 1 (DDB1). Evidence suggests that phytochrome could mediate the production of AS transcripts of SPA3 in response to some light conditions, thus promoting plant photomorphogenesis (Shikata et al 2014). Both IntronR and AltD events were identified in our analysis: the AltD event is conserved across all nine species examined and the IntronR event is conserved in four species: maize, foxtail millet, African oil palm, and Arabidopsis.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Both splice isoforms harbor premature termination codons resulting in truncated proteins that retain interaction with CONSTITUTIVE PHOTOMORPHOGENIC 1 (COPI) but lose the ability to bind to DAMAGED DNA-BINDING PROTEIN 1 (DDB1). Evidence suggests that phytochrome could mediate the production of AS transcripts of SPA3 in response to some light conditions, thus promoting plant photomorphogenesis (Shikata et al 2014). Both IntronR and AltD events were identified in our analysis: the AltD event is conserved across all nine species examined and the IntronR event is conserved in four species: maize, foxtail millet, African oil palm, and Arabidopsis.…”
Section: Resultsmentioning
confidence: 69%
“…This event was also identified in all species examined in our study. Shikata et al (2014) previously characterized IntronR and AltD events within SPA3-a protein that plays a pivotal role in light signaling as a suppressor of photomorphogenesis (Laubinger and Hoecker 2003). Both splice isoforms harbor premature termination codons resulting in truncated proteins that retain interaction with CONSTITUTIVE PHOTOMORPHOGENIC 1 (COPI) but lose the ability to bind to DAMAGED DNA-BINDING PROTEIN 1 (DDB1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phys are involved in germination, de-etiolation, shadeavoidance responses and so on. Recently, it was identified that phy also regulates alternative splicing (Shikata et al 2014). Cry also regulates transcription and mediates various blue light responses including inhibition of hypocotyl elongation, photoperiodic control of floral initiation, circadian rhythms, etc.…”
mentioning
confidence: 99%
“…A number of recent high-profile publications demonstrate the importance of AS and differential functions of AS variants in, for example, organ development (Zhang and Mount, 2009), flowering time control and the circadian clock (Sanchez et al, 2010;James et al, 2012;Posé et al, 2013;Li et al, 2015), light signaling (Shikata et al, 2014), dark-light retrograde signaling from chloroplast to nucleus (Petrillo et al, 2014), and zinc tolerance (Remy et al, 2014). AS of around 18% of Arabidopsis genes generates unproductive mRNA transcript isoforms that are degraded by NMD, which modulates transcript levels thereby regulating levels of protein produced from a gene Drechsel et al, 2013).…”
mentioning
confidence: 99%